PENERAPAN ALGORITMA K-MEANS UNTUK KLASTERISASI DATA OBAT PASIEN RAWAT JALAN BERDASARKAN 3 PENYAKIT TERBANYAK DI RUMAH SAKIT M.NATSIR SOLOK - Hendra Nusa Putra; Ade Wisandra; Fransiska Fransiska (Ensiklopedia of Journal, 2022)
Abstract: The problem at the M. Natsir Solok Hospital is that the officers cannot see many drugs used by the patient, but can only see what drugs the patient has received, so researchers will research so that officers can see what drugs are used by many of them. these 3 diseases. The purpose of this study was to determine the application of drug data clustering based on the 3 most common diseases using the k-means algorithm. This type of research uses descriptive quantitative data. The population of medical record data taken is 1 month, namely in January 2020 as many as 366 medical record data, and the sample is total sampling where all the population is sampled as much as 366 medical record data. The type of data used is secondary data, data collection by observation, and Data analysis using yahoo k-means. The results of the study obtained were the determined clusters of 3 clusters. Among them are Clusters of Low Drug Use, Medium Drug Use, and High Drug Use. Low drug use in cluster A with low drug data use there are 5 types of drugs with a percentage (6%), cluster B high drug data use, there are 74 types of drugs with a percentage (86%), and cluster C moderate drug use data, there are 7 types of drugs with a presentation (8%). It is hoped that the M.Natsir Solok Hospital can apply classification in processing data based on the most diseases so that the hospital can classify types of drugs based on the lowest level of use to the highest level of officers so that they can provide drugs before the drug stock is used up, and can assist officers in reporting SP2TP in M. Natsir Hospital Solok Keywords : Clustering, AlgorithmK-meaning, Disease, Drug, WEKA.